Association of dietary insulinemic potential and colorectal cancer risk in men and women - Tabung, Fred K (Am J Clin Nutr, 2018)
BACKGROUND: Insulin response may be important in colorectal cancer development. Diet modulates insulin response and may be a modifiable factor in colorectal cancer prevention. OBJECTIVE: We examined associations between hyperinsulinemic diets and colorectal cancer risk with the use of an empirical dietary index for hyperinsulinemia (EDIH), a food-based index that characterizes dietary insulinemic potential on the basis of circulating C-peptide concentrations. DESIGN: Diet was assessed every 4 y with food-frequency questionnaires in 46,210 men (Health Professionals Follow-Up Study, 1986–2012) and 74,191 women (Nurses’ Health Study, 1984–2012) to calculate EDIH scores. Multivariable-adjusted Cox regression was used to calculate HRs and 95% CIs for colorectal, proximal/distal colon, and rectal cancer risk. RESULTS: During 26 y of follow-up, we documented 2683 incident colorectal cancer cases. Comparing participants in the highest with those in the lowest quintiles, higher EDIH scores were associated with 33% (men: HR: 1.33; 95% CI: 1.11, 1.61; P-trend = 0.0005), 22% (women: HR: 1.22; 95% CI: 1.03, 1.45; P-trend = 0.01), and 26% (men and women: pooled HR: 1.26; 95% CI: 1.12, 1.42; P-trend <0.0001) higher risk of developing colorectal cancer. The positive associations were limited to the distal colon and rectum in men and to the distal and proximal colon in women; however, combined risk estimates were significant for all anatomic locations except for the rectum. For example, comparing participants in extreme EDIH quintiles, there was no significant association for proximal colon cancer in men (HR: 1.15; 95% CI: 0.84, 1.57; P-trend = 0.32), but the risk was elevated for distal colon (HR: 1.63; 95% CI: 1.14, 2.32; P-trend = 0.002) and rectal (HR: 1.63; 95% CI: 1.09, 2.44; P-trend = 0.01) cancer. Among women, the risk was elevated for proximal (HR: 1.28; 95% CI: 1.00, 1.63; P-trend = 0.03) and distal (HR: 1.46; 95% CI: 1.05, 2.03; P-trend = 0.03) colon cancer but not for rectal cancer (HR: 0.88; 95% CI: 0.60, 1.29; P-trend = 0.61). CONCLUSION: The findings suggest that the insulinemic potential of diet may partly underlie the influence of dietary intake on colorectal cancer development. This observational study was registered at www.clinicaltrials.gov as NCT03364582.